Investigation of Sound Absorption and Impedance Ratio of SBR/HIPS Polymer Blends - TAŞDEMİR, MÜNİR; ERSOY, SEZGİN (TAYLOR & FRANCIS INC, 2012)
A sound absorption material composed of styrene butadiene rubber and high impact polystyrene blend has been developed. With the increased amount of HIPS in SBR/HIPS polymer blends, hardness and Izod impact strength values of the resultant material increased. Sound-absorbing characteristics of SBR/HIPS polymer blends were investigated in the impedance tube, according to transfer function method. The sound absorption coefficients are generally above 0.2 with the maximum of 0.5. It reveals that soft blends have good sound absorption ability in 4000 Hz frequency range. For all groups the least sound absorption rate was seen in the area of 315 Hz at the rate of 0.01. With the increase of frequency for all groups impedance ratio decreased. With addition of SBR rubber to the HIPS, the adhesion and distribution of the present phases were considerably enhanced as well.
Keywords: High impact polystyrene; Impedance ratio; Polymer blends; Sound absorption; Styrene butadiene rubber; Thermoplastic elastomer